2020
DOI: 10.1371/journal.ppat.1008927
|View full text |Cite
|
Sign up to set email alerts
|

Defining the proteolytic landscape during enterovirus infection

Abstract: Viruses cleave cellular proteins to remodel the host proteome. The study of these cleavages has revealed mechanisms of immune evasion, resource exploitation, and pathogenesis. However, the full extent of virus-induced proteolysis in infected cells is unknown, mainly because until recently the technology for a global view of proteolysis within cells was lacking. Here, we report the first comprehensive catalog of proteins cleaved upon enterovirus infection and identify the sites within proteins where the cleavag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
66
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(66 citation statements)
references
References 48 publications
0
66
0
Order By: Relevance
“…CVB3 encodes two distinct proteases, 2A and 3C. These two proteases catalyze the majority of cleavage of the viral polyprotein [ 23 , 24 , 25 ]. Upon entry into the cell, CVB3’s RNA genome is translated by the host cell’s machinery, synthesizing the polyprotein [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CVB3 encodes two distinct proteases, 2A and 3C. These two proteases catalyze the majority of cleavage of the viral polyprotein [ 23 , 24 , 25 ]. Upon entry into the cell, CVB3’s RNA genome is translated by the host cell’s machinery, synthesizing the polyprotein [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…These two proteases catalyze the majority of cleavage of the viral polyprotein [ 23 , 24 , 25 ]. Upon entry into the cell, CVB3’s RNA genome is translated by the host cell’s machinery, synthesizing the polyprotein [ 23 , 24 , 25 ]. 2A performs the primary cleavage of the polyprotein, and 3C catalyzes subsequent polyprotein cleavage [ 23 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…CVB host immune evasion strategies have been described, including the prevention of type I IFN production [30] and early cell death [27,31]. Recent studies have begun to document the scale of disruption that enterovirus encoded proteases can have on host cells through the cleavage of many cellular proteins [29,32]. It is not currently known, however, whether CVBs can also attenuate type III IFN production in IECs, as seen in our experiments conducted in HeLa cells [33].…”
Section: Introductionmentioning
confidence: 84%
“…This lack of response led us to wonder whether CVBs have the capacity to interfere with the ability of IECs to produce IFNs. Many viruses, including CVBs, have developed strategies to evade the host's immune response in order to favor their own replication, including blocking type I and III IFN production and/or signaling [26][27][28][29][30][31]. It has been suggested that the CVB encoded proteases 2A pro and 3C pro are involved in the degradation of proteins involved in virus recognition and the induction of a type I IFN response [30,41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation